Analisis Pengaruh Price Fairness, Service Quality dan Trust terhadap Customer Satisfaction - Zalfa Aini Shaliza; Mazaya Salma; Sarinah Sihombing (Mutiara: Jurnal Ilmiah Multidisiplin Indonesia, 2024)
Consumers who travel frequently (high mobility) use a lot of aviation services, so the aviation business is of interest to many business people. Travel agents are also aggressively providing cheap ticket promotions to attract consumer interest. This creates tough competition between airlines in terms of reasonable prices, best facilities and gaining customer trust. This research aims to determine the influence of Price Fairness, Service Quality, and Trust on Customer Satisfaction of LCC airlines in Indonesia. The research objects of this research are online media libraries, Google Scholar, Semantic Scholar, Elsevier, Zotero and other online journal media. The method used is a literature study, which collects data sources related to the research topic. The literature study aims to explain the main content based on the information obtained. The research results show that Price Fairness, Service Quality, and Trust all have a significant influence on Customer Satisfaction for LCC airlines in Indonesia.